Monolayer MoS2-Based Flexible and Highly Sensitive Pressure Sensor with Wide Sensing Range - Dandan Xu; Ling Duan; Suyun Yan; Yong Wang; Ke Cao; Weidong Wang; Hongcheng Xu; Yuejiao Wang; Liangwei Hu; Libo Gao (Micromachines, 2022)
Flexible pressure sensors play an important role in flexible robotics, human-machine interaction (HMI), and human physiological information. However, most of the reported flexible pressure sensors suffer from a highly nonlinear response and a significant decrease in sensitivity at high pressures. Herein, we propose a flexible novel iontronic pressure sensor based on monolayer molybdenum disulfide (MoS2). Based on the unique structure and the excellent mechanical properties as well as the large intercalation capacitance of MoS2, the prepared sensor holds an ultra-high sensitivity (Smax = 89.75 kPa−1) and a wide sensing range (722.2 kPa). Further, the response time and relaxation time of the flexible sensor are only 3 ms, respectively, indicating that the device can respond to external pressure rapidly. In addition, it shows long-term cycling stability (over 5000 cycles with almost no degradation) at a high pressure of 138.9 kPa. Finally, it is demonstrated that the sensor can be used in physiological information monitoring and flexible robotics. It is anticipated that our prepared sensor provide a reliable approach to advance the theory and practicality of the flexible sensor electronics.